Mecanismos de desgaste, história térmica e ciclo de vida de componentes de um motor de combustão interna de aeromodelo - Lima, Érika Christiane Correia de (2010)
We developed an assay methodology that considered the temperature variation and the scanning electron microscopy as a method to quantify and characterize respectively the consumption evolution in three 46 LA machines, with internal combustion and two-stroke engines, 7.64 cm3 cylinder capacity, 23.0 millimeters diameter and 18.4 millimeters course, RPM service from 2.000 to 16.000 rpm, 1.2 HP power, and 272 grams weight. The investigated engines components were: (1) head of the engine (Al-Si alloy), (2) piston (Al-Si alloy) and (3) piston pin (AISI 52100 steel). The assays were carried out on a desktop; engines 1 and 2 were assayed with no load, whereas in two assays of engine 3 we added a fan with wind speed that varied from 8.10 m/s to 11.92 m/s, in order to identify and compare the engine dynamic behavior as related to the engines assayed with no load. The temperatures of the engine s surface and surroundings were measured by two type K thermopairs connected to the assay device and registered in a microcomputer with data recording and parameters control and monitoring software, throughout the assays. The consumed surface of the components was analyzed by scanning electron microscopy (SEM) and microanalysis-EDS. The study was complemented with shape deformation and mass measurement assays. The temperature variation was associated with the oxides morphology and the consumption mechanisms were discussed based on the relation between the thermal mechanical effects and the responses of the materials characterization